Nikola Mavroyani’nin Eflâk Voyvodalığı (1786-1790) - Sinan YÜKSEL (Gazi Akademik Bakış)
In a period when Russia made its influence increasingly felt in Wallachia and Moldavia following its annexation of Crimea, Nikola Mavroyani desired to be the voivode of Wallachia. In line with this purpose, he both exploited the power of Algerian Gazi Hasan Pasha to the full extent and exercised his diligence to be the Voivode of Wallachia with the support of British and Russian delegates. He eventually achieved his goal on account of Algerian Gazi Hasan Pasha. Serving Ottoman Empire loyally following his voivodship of Wallachia, Mavroyani drew reactions from both Boyars and people regarding his practices in Wallachia. Boyars and people requested Russia to relieve Mavroyani of his voivodship by bringing complaints to Ivan Severin, the Russian consul in Wallachia. On the other hand, Mavroyani tried to deceive Istanbul by receiving letters from Boyars stating that they are pleased with himself at certain intervals. Ottoman Government warned Mavroyani several times and demanded him to relieve his administrative approach -pressure- on people and Boyars. Considering these warnings, Mavroyani had to relieve his pressure on people and Boyars even a little. In the Ottoman-Russo-Austro wars that erupted in 1787, Mavroyani tried to defend Wallachia and its districts with an army consisting of more than forty thousand soldiers whose expenses were paid out of his own pocket and won a remarkable victory over Austria. His loyalty and struggle during the war won recognition by both Abdulhamid I and Sultan Selim. He brought complaints to Istanbul regarding the generals failing in the war through the courage he took from his achievements in these wars and Algerian Gazi Hasan Pasha, and this action paved the way for his fall. He was executed by Serif Hasan Pasha, who became the grand vizier after Algerian Gazi Hasan Pasha, with the claim that he was going to flee with a substantial amount of jewelry. In the investigation carried out following his execution, it was understood that he was not that wealthy at all.